Optimization of excimer-forming two-probe nucleic acid hybridization method with pyrene as a fluorophore. - Masuko, M (1998)
A previously presented homogeneous assay method, named the excimer-forming two-probe nucleic acid hybridization (ETPH) method, is based on specific excimer formation between two pyrenes attached at the neighboring terminals of two sequential probe oligonucleotides complementary to a single target. In this study, we investigated assay conditions and optimal molecular design of probes for intense excimer emission using a pyrenemethyliodoacetamide-introduced 16mer probe, a pyrene butanoic acid-introduced 16merprobe and a target 32mer. The length of the linker between the pyrene residue and the terminal sugar moiety remarkably influenced the quantum efficiency of excimer emission; the pair of linker arms of these two probes was optimal. The quantum efficiency was also dependent upon the concentrations of dimethylformamide and NaCl added to the assay solution. Spectroscopic measurements and T m analysis showed that an optimal configuration of the two pyrene residues for intense excimer emission might be affected by pyrene-pyrene interaction, pyrene-duplex interaction (intercalation/stacking) and solvent conditions as a whole. We then demonstrated the practicality of the ETPH method with the optimal hybridization conditions thus attained by determining that the concentration of 16S rRNA in extracts from Vibrio mimicus ATCC 33655 cells in exponential growth phase is 18 500 16S rRNA molecules/cell on average.